The association between post-cardiac arrest cerebral oxygenation and survival with favorable neurological outcomes: A multicenter study. (September 2020) - Tran, Linh N.; Patel, Jignesh; Yang, Jie; O'Neill, Caitlin; Yin, Donglei; Nguyen, Robert; Pogson, David; Deakin, Charles; Harris, Tim; Brett, Stephen J.; Page, Valerie; Parnia, Sam
Abstract: Objective: Cerebral oximetry is a non-invasive system that uses near infrared spectroscopy to measure regional cerebral oxygenation (rSO2 ) in the frontal lobe of the brain. Post-cardiac arrest rSO2 may be associated with survival and neurological outcomes in out-of-hospital cardiac arrest patients; however, no studies have examined relationships between rSO2 and neurological outcomes following in-hospital cardiac arrest (IHCA). We tested the hypothesis that rSO2 following IHCA is associated with survival and favorable neurological outcomes. Design: Prospective study from nine acute care hospital in the United States and United Kingdom. Patients: Convenience sample of IHCA patients admitted to the intensive care unit with post-cardiac arrest syndrome. Interventions: Cerebral oximetry monitoring (Equanox 7600, Nonin Medical, MN, USA) during the first 48 h after IHCA. Measurements and Main Results: Subject's rSO2 was calculated as the mean of collected data at different time intervals: hourly between 1−6 h, 6−12 h, 12−18 h, 18−24 h and 24−48 h. Demographic data pertaining to possible confounding variables for rSO2 and primary outcome were collected. The primary outcome was survival with favorable neurological outcomes (cerebral performance scale [CPC] 1−2) vs severe neurological injury or death (CPC 3−5) at hospital discharge. Univariate and multivariate statistical analyses were performed to correlate cerebral oximetry values and other variables with the primary outcome. Among 87 studied patients, 26 (29.9%) achieved CPC 1−2. A significant difference in mean rSO2 was observed during hours 1−2 after IHCA in CPC 1−2 vs CPC 3−5 (73.08 vs. 66.59, p = 0.031) but not at other time intervals. There were no differences in age, Charlson comorbidity index, APACHE II scores, CPR duration, mean arterial pressure, PaO2, PaCO2, and hemoglobin levels between two groups. Conclusions: There may be a significant physiological difference in rSO2 in the first two hours after ROSC in IHCA patients who achieve favorable neurological outcomes, however, this difference may not be clinically significant.